Acute effects of loaded whole body vibration schemes on countermovement jump, speed and agility - Edin Uå½ıäœanın; Fuad Babajıä†; Haris Pojskıä†; Jeffrey Pagaduan; Mario Tomljanovıä†; Melika Muratovıä† (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to compare the effects of loaded whole body static squat exercise during whole body vibration and non-vibration schemes on countermovement jump (CMJ), speed and agility. Twenty-one healthy male college football players (age: 20.14 ± 1.65 years; body height: 179.9 ± 8.34 cm; body mass: 74.4 ± 13.0 kg; % body fat: 9.45 ± 4.8) participated in the study. They underwent a standardized general warm-up and dynamic stretching followed by randomized loaded protocols executed for 5 minutes with a rest interval of 30 seconds. These included static squat with 30% bodyweight external load (ST + 30%), ST + 30% on a vibration platform at 25 Hz and 2 mm (WBV25), and  ST + 30% on a vibration platform at 50 Hz and 4mm. Measurement of  CMJ, 15 m sprint and modified agility tests followed the warm-up protocol. One way repeated measures ANOVA revealed a significant difference on CMJ performance, F(2,40) = 24.5, partial Î·2 =  .551, p lt; 0.01. Bonferonni post hoc showed that ST+30% posted significantly lower CMJ than WBV25 and WBV50. CMJ at WBV50 was higher than WBV25. There was a significant difference on speed, F(2, 40) = 23.6, partial Î·2  = .542, p lt; 0.01. Post hoc determined that ST+30% was significantly slower than WBV25 and WBV50. WBV50 was faster than WBV25. There was a significant difference in the agility among interventions, F(2, 40) = 18.2, partial Î·2 = .477, p lt; 0.01. ST+30% agility time was significantly higher compared to WBV25 and WBV50.  In conclusion, WBV50 posted the greatest benefits in CMJ, speed and agility.